Photodynamic therapy with methyl aminolaevulinate 80 mg g−1 for severe facial acne vulgaris: a randomized vehicle‐controlled study. (1st April 2016) - Pariser, D.M.; Eichenfield, L.F.; Bukhalo, M.; Waterman, G.; Jarratt, M.; ,; Bhatia, A.; Greenstein, D.; Hamzavi, F.; Kantor, J.; Speelman, P.N.; Murakawa, G.J.; et al.
Summary: Background: Severe acne vulgaris has limited therapeutic options. Objectives: To evaluate photodynamic therapy (PDT) using topical methyl aminolaevulinate (MAL, 80 mg g − 1 ) as the photosensitizer in severe facial acne. Methods: A double‐blind, randomized, vehicle‐controlled multicentre trial in 153 patients (aged 12–35 years) with severe facial acne [Investigator's Global Assessment (IGA) score 4; 25–75 inflammatory lesions with ≤ 3 nodules; 20–100 noninflammatory lesions]. Treatment (four treatments 2 weeks apart) involved incubation with MAL ( n = 100) or vehicle cream ( n = 53) for 1·5 h under occlusion, then illumination (635‐nm red light, total dose 37 J cm − 2 ). IGA assessment and standardized lesion counts were performed before each treatment and 12 weeks after the first treatment. Treatment success was defined as improvement from baseline in IGA by ≥ 2 grades at 12 weeks. Safety assessments were for pain (10‐cm visual analogue scale, immediately after illumination), erythema (four‐point rating scale) and adverse events. Results: At 12 weeks, PDT using MAL 80 mg g − 1 reduced inflammatory lesions vs. vehicle PDT (mean change −15·6 vs. −7·8, P = 0·006; mean percentage change −37·3% vs. −16·2%, P = 0·003). However, noninflammatory lesions did not decrease significantly (mean change −11·8 vs. −10·7, P = 0·85; mean percentage change −28·6% vs. −24·9%, P = 0·72). Treatment success rates were greater with MAL‐PDT 80 mg g −1 (44% vs. 26%, P = 0·013). Pain was low and manageable by briefly pausing illumination. There was similar pain or erythema with successive treatments. Conclusions: PDT using topical MAL 80 mg g −1 and red light may offer promise for severe acne vulgaris.